2020
DOI: 10.1021/acsomega.0c00063
|View full text |Cite
|
Sign up to set email alerts
|

Red-Emission Probe for Ratiometric Fluorescent Detection of Bisulfite and Its Application in Live Animals and Food Samples

Abstract: Key roles of bisulfite (HSO 3 − ) in food quality assurance and human health necessitate a reliable analytical method for rapid, sensitive, and selective detection of HSO 3 − . Herein, a new red-emitting ratiometric fluorescence probe, BIQ, is reported for sensitive and selective detection of HSO 3 − in food samples and live animals. Probe BIQ recognizes HSO 3 − via a 1,4-nucleophilic addition reaction. As a result of this specific reaction, emission intensities at 625 and 475 nm are dramatically changed, allo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(7 citation statements)
references
References 58 publications
1
6
0
Order By: Relevance
“…1,2 As antioxidants and antimicrobial agents, HSO 3 − /SO 3 2− has been frequently used to inhibit enzymatic reactions and prevent microbial growth and oxidation during production and storage of foodstuff. 3,4 There are a number of foods that contain high amounts of bisulfite/sulfite (>100 mg/L) including wine, dried fruits, pickled cocktail onions, molasses, non-frozen lemon juice, and so forth. 5 However, human health will be affected by an extensive intake of HSO 3 − /SO 3 2−…”
Section: ■ Introductionsupporting
confidence: 61%
“…1,2 As antioxidants and antimicrobial agents, HSO 3 − /SO 3 2− has been frequently used to inhibit enzymatic reactions and prevent microbial growth and oxidation during production and storage of foodstuff. 3,4 There are a number of foods that contain high amounts of bisulfite/sulfite (>100 mg/L) including wine, dried fruits, pickled cocktail onions, molasses, non-frozen lemon juice, and so forth. 5 However, human health will be affected by an extensive intake of HSO 3 − /SO 3 2−…”
Section: ■ Introductionsupporting
confidence: 61%
“…Comparison of probe PBI with some reported probes toward HSO 3 − As shown in Table 1, in terms of excitation wavelength/emission wavelength, detection medium, response type, pH, detection limit and cell application, probe PBI had good analytical performance compared with other HSO 3 − uorescent probes reported recently. [40][41][42][43][44][45] The result showed that probe PBI was a ratiometric uorescent probe with a low detection limit (208 nmol/L). Moreover, biological experiments have demonstrated the application of probe PBI in monitoring intracellular HSO 3 − .…”
Section: The Detection Of Hso 3 − In Living Cellsmentioning
confidence: 98%
“…Consequently, the detection of HSO 3 – is of great significance and required in both food samples and biological system. Up to now, many detection methods, such as fluorescent probes and chromatometry, have been utilized to determine HSO 3 – in living cells and in food samples. However, fluorescence techniques have limits such as low signal-to-noise ratio, false-positive (background) signals, and difficulty in labeling probes; the preparation of nanoparticles, complicated sample pretreatment, and low sensitivity of colorimetric sensors still restrict their applications.…”
Section: Polymeric Nanochannel-based Biosensing Platforms For Detecti...mentioning
confidence: 99%